2017
DOI: 10.1103/physrevd.95.076015
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg-Euler effective action in slowly varying electric field inhomogeneities of Lorentzian shape

Abstract: We use a locally constant field approximation (LCFA) to study the one-loop Heisenberg-Euler effective action in a particular class of slowly varying inhomogeneous electric fields of Lorentzian shape with 0 ≤ d ≤ 4 inhomogeneous directions. We show that for these fields, the LCFA of the Heisenberg-Euler effective action can be represented in terms of a single parameter integral, with the constant field effective Lagrangian with rescaled argument as integration kernel. The imaginary part of the Heisenberg-Euler … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Our result for the probability P v (67) coincides with the one obtained in Ref. [31] for the particular case of d = 4.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our result for the probability P v (67) coincides with the one obtained in Ref. [31] for the particular case of d = 4.…”
Section: Introductionsupporting
confidence: 90%
“…The representations (57) and (59) coincide with the vacuum-to-vacuum transition probabilities obtained from the imaginary part of a locally constant field approximation (LCFA) for the one-loop effective action in d = 4 dimensions [22,31]. In this approximation, the effective action S is expanded about the constant field case, in terms of derivatives of the background field strength F µν ,…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…These have been used to study low energy photon amplitudes [24,25] and the structure of the quantum vacuum, see [26] for a recent review. Aside from this, the particle propagator can also be constructed exactly (non-perturbatively) in the presence of constant fields, plane waves, and other symmetric fields, allowing the calculation of a variety of electron-seeded and photon-seeded processes, see [26][27][28][29] for reviews.Recently, however, it was found that historical calculations had overlooked the possibility of one particle reducible (1PR) contributions to processes in constant background fields [30][31][32]. These contributions involve a tadpole, displayed in figure 1, attached somewhere in the corresponding Feynman diagram describing the process.…”
mentioning
confidence: 99%